Development of Integrating Innovation of Education Technology Model in Chinese Higher Education Institutions - Yang, Yang; Petsangsri, Sirirat; Ratana-Olarn, Thanin; Cui, Jianming (My University, 2024)
Given the rapid advancement of technology today, universities must stay up to date with these developments to enhance their management practices. Thereby, this study aimed to develop the model for integrating innovation of education technology in Chinese higher education institutions by synthesizing the concepts of personnel management practices, organization structure & culture, integration and innovation of education technology, and technological landscape through a literature review, and a semi-structured interview consisting of 20 experts has been organized to develop the model. Besides that, 5 experts from different Chinese universities have participated in a focus group to further discuss and validate the developed model. As a result, the developed model has been confirmed as of good quality.
Keywords: Chinese higher education institutions; Integration and innovation of education technology; Organization structure & culture; Personnel management practices; Technological landscape